Balanced Reputation Management Strategy: A Cross-Site Case Study of Branding Image for Competitive Advantage in Indonesian Islamic Higher Education Institutions - Rachman, Poppy; Abidin, Munirul; Khudori Soleh, Achmad; Murfi, Ali (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to examine branding image strategies in building competitive advantage at Private Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Swasta or PTKIS) in Indonesia. The research focuses on Universitas Islam Zainul Hasan Genggong (UNZAH) and Sekolah Tinggi Dirasat Islamiyah Imam Syafi’i (STDIIS) Jember, which adopt both local and global branding approaches. This study responds to the need for a balanced reputation management model to strengthen PTKIS’s positioning amidst the dynamics of national and global higher education landscapes. Design/methods/approach – Employing a qualitative approach with a multi-case study design and cross-site analysis, data were collected through in-depth interviews, participatory observation, and analysis of strategic documents. Data analysis followed the Miles & Huberman interactive model, and validation was conducted through source triangulation. Findings – UNZAH successfully established its institutional identity through the integration of local and Islamic cultural values, leading to an increase of up to 1,000 new student enrollments per year. STDIIS developed a global branding strategy through Arabic language proficiency and a Madinah-based curriculum, attracting over 1,200 applicants. The conceptual model of Balanced Reputation Management Strategy was formulated to integrate local characteristics and global strategies within the institutional branding framework. Research implications – This model can be implemented by PTKIS administrators as a guideline for designing long-term branding strategies grounded in Islamic values, local culture, and international competitiveness, in order to strengthen institutional image and attract prospective students.